Olive Mill Wastewater as Renewable Raw Materials to Generate High Added-Value Ingredients for Agro-Food Industries - Paola Foti; Flora V. Romeo; Nunziatina Russo; Alessandra Pino; Amanda Vaccalluzzo; Cinzia Caggia; Cinzia L. Randazzo (Applied Sciences, 2021)
Olive oil production represents an agro-industrial activity of vital economic importance for many Mediterranean countries. However, it is associated with the generation of a huge amount of by-products, both in solid and liquid forms, mainly constituted by olive mill wastewater, olive pomace, wood, leaves, and stones. Although for many years olive by-products have only been considered as a relevant environmental issue, in the last decades, numerous studies have deeply described their antioxidant, anti-inflammatory, immunomodulatory, analgesic, antimicrobial, antihypertensive, anticancer, anti-hyperglycemic activities. Therefore, the increasing interest in natural bioactive compounds represents a new challenge for olive mills. Studies have focused on optimizing methods to extract phenols from olive oil by-products for pharmaceutical or cosmetic applications and attempts have been made to describe microorganisms and metabolic activity involved in the treatment of such complex and variable by-products. However, few studies have investigated olive oil by-products in order to produce added-value ingredients and/or preservatives for food industries. This review provides an overview of the prospective of liquid olive oil by-products as a source of high nutritional value compounds to produce new functional additives or ingredients and to explore potential and future research opportunities.